Water pricing issues in countries with water deficit - Polycarpou P. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
In the Mediterranean countries water management is not only a matter of setting the price of water, but also of securing the availability of water. In Cyprus, water supply is based on rainfall that is becoming less and less with time. Water pricing should take into account covering the primary costs for the acquisition of water such as the cost of the distribution networks, running costs for pumps, and the intended use of the water (agriculture, industry, tourism, households and so on). Households have the right to be supplied with water of good quality at reasonably low prices. Water used for industry and other economic activities should be priced at its real cost, increased by an availability factor that takes into account the available water reserves of the country. A good water policy should promote issues such as: saving water in all sectors of economy and preventing irrational water use (through proper water pricing schemes, etc.); minimizing distribution network losses; safeguarding the quality of water reserves (during water production, distribution, storage, water treatment and reuse). All water resources in a country should be considered as a national resource and should be controlled by a single entity to achieve good coordination and management. This paper deals with a simplified method for water pricing, in cases of water scarcity as encountered in the Mediterranean countries.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)